Steel rebar categories data and statistical properties of Nigerian reinforcement used for structural strength - Ehizemhen Igibah, Christopher; Omolayo Agashua, Lucia; Abubakar Sadiq, Adavudi (International Journal of Engineering and Technology, 2019)
The paper was aimed at evaluating effect of cost prices of reinforcement on its strength since dispersal in the size geometry of locally available and imported bars is very essential to the development of stable standard of practice for both civil and building engineering sector. Steel rebar from some locations in Lagos state, Nigeria was obtained so as to determine its cost price and strength. The results disclosed that both yield and ultimate loads of 45.67 and 65.54% respectively, as regards to flexural strength, Ogba reinforcement is the highest.
Keywords: Reinforcement; Steel Rebar; Structural Strength; Lagos; Nigeria.